Towards a full recognition of the peasant rondas and legal pluralism - Yrigoyen Fajardo, Raquel (2002)
The objective of this text is to explain the nature of the Andean community institution that the peasant patrols have in order to support their demands for constitutional and legal recognition. This analysis starts from a pluralist interpretation of the Constitutional Charter of 1993 and the ILO Convention 169, in order to enrich the debate on the ongoing constitutional reform. The peasant patrols constitute a widespread form of Andean communal institution that exercises functions of local government, justice, local development, dialogue with the state and supra-local articulation.